Study the Effect of pH on the Fermentation Anaerobic-Aerobic Siwalan (Borassus flabellifer L.) Sap to Produce Acetic Acid - Elly Agustiani; Destri Susilaningrum; Atiqa Rahmawati; Fibrillian Z.L.; Dimas L.R. (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2020)
This research is to study the effect of ethanol fermentation aerobic pH on acetic acid product. Anaerobic fermentation uses saccharomyces cerevisiae to produce ethanol, and aerobic fermentation uses acetobacter acetic for acetic acid production. In aerobic ethanol fermentation using pH 3; 3.5; 4 and 5. The ethanol concentration was evaluated using GC ULTRA Scientific Gas Chromatography, DSQ II detector, and MS 220 column. Acetic acid produced was analyzed using an alkalymetric method. Anaerobic fermentation uses Saccharomyces cerevisiae with 1-day log phase, while aerobic fermentation uses acetobacter aceti with a 5-day log phase. Fermentation using saccharomyces cerevisiae within 24 hours so that reduction sugar could stably decrease, optimum ethanol could be got at optimum pH 6 which could decrease 55 % of reducing sugar concentration to produce 8,20583 %v/v ethanol. Fermentation acetate acid content observed in 3 days at pH 6 and 30 ⁰C will produce 6,659 g/l also shows that pH 4-6 at 30 ⁰C will produce 6,605 g/l acetate acid. Aerobic fermentation of acetate acid in 3 days shows that pH 4-6 is highly affected by temperature at 30⁰C. Statistical analysis shows, in ethanol production pH and fermentation time give significant effect, but interaction has no significant effect.